Georgia : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper assesses macroeconomic and structural reforms in Georgia. The government's reform package includes a fiscal policy within a declining deficit path which intends to incentivize private investment, a scaling up of public investment, improvement in government's efficiency, and an education reform. Based on modeling analysis, the implementation of this package will provide significant benefits to the economy. Over the long term, real GDP is estimated to be about 5 percent higher than in the baseline and-in the path toward the new equilibrium-annual growth about 0.7 percentage points higher over the medium term. The education reform has sizeable effects, but they only come into effect in the long term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet